Peran Keluarga dan Pengurus Panti Sosial Tresna Werdha Wana Seraya Kota Denpasar dalam Program Perawatan Lanjut Usia - Lydia Sloan Marbun; Ida Ayu Alit Laksmiwati; Putu Karina Pravitasari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes the role of families and caregivers at Panti Sosial Tresna Werdha Wana Seraya Denpasar in implementing elderly care programs and examines the implications of these programs for the quality of life of older adults. Using a qualitative method with an ethnographic approach, data were collected through participant observation, in-depth interviews, and documentation. Two theoretical frameworks guided the analysis: Carrolyn Smith-Morris’ Social Support Theory, which highlights the importance of emotional, informational, and instrumental support for elderly well-being, and Robert J. Havighurst’s Activity Theory, which states that active involvement in social, physical, and spiritual activities enhances happiness and life satisfaction in old age. The findings show that families’ involvement remains limited due to time and distance constraints, yet their emotional presence still contributes positively to the psychological comfort of the elderly. Caregivers play a dominant role in meeting the physical, social, emotional, and spiritual needs of residents. The care program demonstrates positive implications, including improved health stability, increased social interaction, strengthened feelings of appreciation, and enhanced spiritual peace. Additionally, Balinese cultural values such as tatwam asi and menyama braya reinforce empathy, togetherness, and respectful relationships within the care system. The study concludes that synergy between families, caregivers, and local cultural values forms a crucial foundation for a meaningful and humane elderly care system.